Genetic characterisation of Ugandan strains of Colletotrichum sublineolum using ISSR makers - Sserumaga, J.P.; Biruma, M.; Akwero, A.; Okori, P.; Edema R. (African Journals Online (AJOL), 2013)
Colletotrichum sublineolum, the causal agent of sorghum anthracnose, presents high variability, genetic instability and host specialisation, hence rapidly breaking down resistance. In Uganda, no population studies of Colletotrichum sublineolum have been reported hence there is limited information on the nature of epidemics and pathogen. The present study aims at investigating the genetic diversity within 124 Colletotrichum sublineolum isolates from Uganda. The intersimple sequence repeats (ISSR) produced 37 polymorphic loci and neighbor-joining analysis revealed two major groups. There were no major groups among all isolates in studies. Analysis of molecular variation (AMOVA) based on 7 agro-ecologies of Uganda revealed the presence of a population structure, (FFST = 0.08 P = 0.05) leading to acceptance of null hypothesis stating a presence of population differentiation between the agro-ecologies in Uganda. Gene flow between agro-ecologies was 5.75 calculated from ÔFST. The results of the AMOVA analysis revealed the allelic variation (92.5%) was shared between populations. Average gene diversity over all loci ranged from 0.192 to 0.335 showing high diversity within population rather than between populations. The numbers of polymorphic loci were similar for the population studied.